Atomically precise nanoclusters with reversible isomeric transformation for rotary nanomotors - Zhaoxian Qin (Nature Portfolio, 2020)
Atomically precise metal nanoclusters are an emerging class of precision nanomaterials and hold potential in many applications. Here, the authors devise a [Au13Ag12(PPh3)10Cl8]+ nanocluster with two conformational isomers that can reversibly convert in response to temperature, and hence acts as a rotary nanomotor.